2018
DOI: 10.4269/ajtmh.17-0974
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost, Community Knowledge Approach to Estimate Maternal and Jaundice-Associated Mortality in Rural Bangladesh

Abstract: In the absence of a civil registration system, a house-to-house survey is often used to estimate causespecific mortality in low-and middle-income countries. However, house-to-house surveys are resource and time intensive. We applied a low-cost community knowledge approach to identify maternal deaths from any cause and jaundiceassociated deaths among persons aged ³ 14 years, and stillbirths and neonatal deaths in mothers with jaundice during pregnancy in five rural communities in Bangladesh. We estimated the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In the CKA study from Bangladesh, deaths of women reported by community groups was compared with records of those deaths in local health facilities to determine the accuracy of those reports. 26 In contrast, our study was unable to compare reported deaths of FSW from the community with health facility documentation of the deaths as many FSW die outside of medical facilities. In our study, when the specific location of death was reported, only 280 deaths (13·3%) occurred at the hospital.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In the CKA study from Bangladesh, deaths of women reported by community groups was compared with records of those deaths in local health facilities to determine the accuracy of those reports. 26 In contrast, our study was unable to compare reported deaths of FSW from the community with health facility documentation of the deaths as many FSW die outside of medical facilities. In our study, when the specific location of death was reported, only 280 deaths (13·3%) occurred at the hospital.…”
Section: Discussionmentioning
confidence: 86%
“…Although this study did not include an economic analysis of using the CKA or validate its use to identify all causes of death among FSW, the CKA is reported to be a less expensive and faster alternative to labor-intensive household surveys while also being highly sensitive. 26 In addition, other studies confirm that community informants can reliably report maternal deaths at a lower cost than other more labor intensive methods. 20 While there are other methods for identifying maternal deaths, including the Maternal Death Surveillance Finally, studies early in the COVID-19 pandemic reported an increase in maternal deaths related to compromised access to health services resulting from lockdowns, disruption of clinical care, and fear of being infected with the virus at health care facilities.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations